Initial teacher training: meanings and singularities of scientific initiation as a science policy - Azevedo, Tereza Hortencia da Silva; Nascimento, Marilene Batista da Cruz; Lopes, Julita Batista da Cruz (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
This research aims to understand the meanings and singularities (re)constructed by scientific initiation (SI) scholarship holders/volunteers, with a view to identifying interrelations with initial teacher education. This is a theoretical-empirical study, of qualitative nature, which used a questionnaire as an instrument for the collection of data worked in the light of discursive textual analysis (ATD). The findings allow us to conclude that the experiences experienced in SI by the participants present an athedinal tendency towards the academic career, also focused on professional values, respecting the curriculum and pedagogical practices; learning for authorship, interaction and critical relationship; production and dissemination of knowledge and social pertinence for the performance in the spaces of the profession. It was concluded that the initial training of teachers refers to considering the difficulties existing in the research process of the students and in the work of the teacher-advisor on the construction of knowledge with the world, with himself and with theother.